Optimisation of hybrid surfactant chemical structure for water-in-C02 microemulsions stabilisation - Tretya Ardyani (Tanjong Malim, 2015)
Optimisation of hybrid surfactant chemical structure for water-in-C02 microemulsions stabilisation by Tretya Ardyani